Investigator Issue in Financial Service Crime in Indonesia - Wiriadinata, Wahyu, Mr. (Indonesia Law Review, 2014)
The objective of this paper is to address a question of the effectiveness of Financial Service Authority (Otoritas Jasa Keuangan - OJK) investigators in eradicating financial service crimes in Indonesia. This question arises because in Law on Financial Service Authority there are OJK’s investigators with an investigatory authority on OJK crimes, including, banking, capital market, insurance, pension fund, financing institutions, and other financial service institution sectors. Meanwhile, there have been other investigators with an authority to investigate, namely, public prosecutor, police, and KPK (Indonesia’s corruption eradicating commission). The theoretical framework of this paper was grounded in the thoughts of Aristotle, who says that the goal of law is to achieve justice, and that of Hans Kelsen’s stuffen theory. The method of writing was juridical-normative, by studying legislations, both contained in laws themselves and in literatures/books of legal science, particularly those related to Financial Service Authority. The result was in a form of juridical aspect and written in a descriptive-analytical form. The conclusion of this paper was as follows: There was an overlapping of authorities between OJK’s investigators and public attorney’s investigators, police, and KPK, be they in the investigation of general crimes and that of special crimes/corruption. As for the effectiveness of OJK’s investigators, it should be proved yet in the future.